In this mini-lesson, we will explore what is x squared, the difference of squares, and solving quadratic by completing the squares.

In algebra, we commonly come across the term x squared. Do you aware of what is x squared?

We are going to learn particularly about \(x^2\) in this mini-lesson.

**Lesson Plan**

1. | What is x Squared? |

2. | Important Notes on x Squared |

3. | Solved Examples on x Squared |

4. | Challenging Questions on x Squared |

5. | Interactive Questions on x Squared |

**What is x squared?**

xsquared is a notation that is used to represent the expression \(x\times x\).

i.e., xsquared equals xmultiplied by itself.

In algebra, \(x\) multiplied by \(x\) can be written as\(x\times x\) (or)\(x\cdot x\) (or)\(x\, x\) (or)\(x(x)\)

\(x\) squared symbol is \(x^2\).

Here:

- \(x\) is called the base.
- 2 is called the exponent.

\(x\) squared = \(x^2\) =\(x\times x\)

Here are some examples to understand \(x\) squared better.

Phrase | Expression |
---|---|

xsquared times x | \(x^2\times x =x^3\) |

xsquared minusx | \(x^2-x\) |

xsquared divided byx | \(x^2\div x =x^1=x\) |

xsquared timesxsquared | \(x^2\times x^2 =x^4\) |

xsquared plus xsquared | \(x^2+x^2 =2x^2\) |

xsquared plus ysquared | \(x^2+y^2\) |

square root x^{2} | \(\sqrt{x^2}=x\) |

xsquared times x cubed | \(x^2\times x^3 =x^5\) |

Important Notes

**Here we use the laws of exponents in case of multiplying or dividing the exponents of the same base.**

\[\begin{aligned}

x^{m} \cdot x^{n} &=x^{m+n} \\

\frac{x^{m}}{x^{n}} &=x^{m-n}

\end{aligned}\]**The formulas for the squares of the sum and the difference are:**

\[\begin{array}{l}

(x+y)^{2}=x^{2}+2 x y+y^{2} \\

(x-y)^{2}=x^{2}-2 x y+y^{2}

\end{array}\]

**Is x Squared Same as 2x?**

No, \(x^2\) is NOT same as \(x\).

Using the exponents, \(x^2 = x \times x \).

But \(2x = 2 \times x= x + x\), because multiplication is nothing but the repeated addition.

Here are some examples to understand it better.

\(x\) | \(x^2 = x \times x\) | \(2x = 2\times x\) |
---|---|---|

3 | \(3 \times 3=9\) | 2(3) = 6 |

-1 | \(-1\times -1 = 1\) | 2(-1) = -2 |

-2 | \(-2\times -2 =4\) | 2(-2) = -4 |

**Special Factoring: Differenceof Squares **

While factoring algebraic expressions, we may come across an expression that is a difference of squares.

i.e., an expression of the form \(x^2-y^2\).

There is a special formula to factorize this:

\(x^2-y^2=(x+y)(x-y)\)

Here are some examples to understand it better.

\(x^2-y^2\) | \((x+y)(x-y)\) |
---|---|

\(x^2-3^2\) | \((x+3)(x-3)\) |

\(y^2-x^2\) | \((y+x)(y-x)\) |

\(x^2-4y^2\) | \((x+2y)(x-2y)\) |

**Solving Quadratics by Completing the Square**

Completing the square in a quadratic expression \(ax^2+bx+c\) means expressing it of the form \(a(x+d)^2+e\).

Let us learn howtocomplete asquare using an example.

**Example**

Complete the square in the expression

\[-4 x^{2}-8 x-12\]

**Solution:**

First, we should make sure that the coefficient of \(x^2\) is \(1\)

If the coefficient of \(x^2\) is NOT\(1\), we will place the numberoutside as a common factor.

We will get:

\[-4 x^{2}-8 x-12 = -4 (x^2+2x+3)\]

Now, the coefficient of \(x^2\) is \(1\)

**Step 1: Find half of the coefficient of \(x\)**

Here, the coefficient of \(x\) is \(2\)

Half of \(2\)is \(1\)

**Step 2: Find the square ofthe above number**

\[1^2=1\]

**Step 3: Add and subtract the above number after the \(x\) term in the expression whose coefficient of \(x^2\) is \(1\)**

\[\begin{align} -4 (x^2\!+\!2x\!+\!3)\!&=\!\!-4 \left(x^2\!+\!2x\! +\color{green}{\mathbf{1 -1}} \!+\!3 \right)\end{align}\]

**Step 4: Factorize the perfect square trinomial formed by the first 3 terms using the identity \( x^2+2xy+y^2=(x+y)^2\)**

In this case, \[x^2+2x+ 1= (x+1)^2\]

The above expression fromStep 3 becomes:

\(-4 \left(\color{green}{x^2\!+\!2x \!+\!1\!}-\!1 \!+3\right)\)=\(-4 (\!\color{green}{(x+1)^2}\!\! -\!1+3\!)\)

**Step 5: Simplify the last two numbers.**

Here, \(-1+3=2\)

Thus, the above expression is:

\[ -4 (x+1)^2 \color{green}{-1+3} = -4 ((x+1)^2 +\color{green}{2}) \\= -4(x+1)^2-8\]

This is of the form \(a(x+d)^2+e\).

Hence, we have completed the square.

Thus, \(-4 x^2-8 x-12= -4 (x+1)^2 -8)\)

Here is the completing the squarecalculator.We can enter any quadratic expression here and see how the square can be completed..

**Solved Examples**

**Example 1**

Can we help Sophia to understand \(x^2\) and \(2x\) don't need to be the same by evaluating them at\(x= -6\)?

**Solution**

It is given that \(x=-6\).

Then:

\[\begin{align} x^2 &= (-6)^2 = -6 \times -6 = 36\\[0.2cm]

2x &= 2(-6) = 2 \times -6 = -12\end{align}\]

Here, \(x^2 \neq 2x\).

Therefore,

\(x^2\) and \(2x\) don't need to be the same

**Example 2**

Can we help Jim to factorize the following expression using the formula of difference of squares?

\[x^4-16\]

**Solution**

The formula of difference of squares says: \[x^2-y^2=(x+y)(x-y)\]

We will apply this to factorize the given expressions as many times as needed.

\[\begin{align}

x^4-16 &= (x^2)^2 - 4^2\\[0.2cm]

&= (x^2+4)(x^2-4)\\[0.2cm]

&=(x^2+4)(x^2-2^2)\\[0.2cm]

&=(x^2+4)(x+2)(x-2)

\end{align}\]

Therefore, the given expression can be factorized as

\((x^2+4)(x+2)(x-2)\)

**Example 3**

The area of a square-shaped window is 36 square inches. Can you find the length of the window?

**Solution**

Let us assume that the length of the window is \(x\) inches.

Then its area using the formula of area of a square is \(x^2\) square inches.

By the given information, \[x^2= 36\]

By taking the square root on both sides, \[ \sqrt{x^2}= \sqrt{36}\]

We know that the square root of \(x^2\) is \(x\).

The square root of 36 is 6 because \(6^2=36\).

Therefore,

\(\therefore\) The length of the window = 6 inches

**Example 4**

Solveby completing the square.

\[x^2-10x+16=0\]

**Solution**

The given quadratic equation is:

\[x^2-10x+16=0\]

We will solve by completing the square.

Here, the coefficient of \(x^2\) is already \(1\)

The coefficient of \(x\) is \(-10\)

The square of half of it is \((-5)^2 =25\)

Adding and subtracting it on the left-hand side of the given equation after the \(x\) term:

\[ \begin{aligned} x^2-10x+25-25+16&=0\\[0.2cm](x-5)^2-25+16&=0\\ [\because x^2\!-\!10x\!+\!25\!=\! (x\!-\!5)^2 ]\\[0.2cm] (x-5)^2-9&=0\\[0.2cm] (x-5)^2& =9 \\[0.2cm] (x-5) &= \pm\sqrt{9} \\ [ \text{Taking square root }&\text{on both sides} ]\\[0.2cm] x-5=3; \,\,\,\,&x-5= -3\\[0.2cm] x=8; \,\,\,\,&x = 2 \end{aligned} \]

\(\therefore\) \(x=8,\, \, 2\)

Challenging Questions

**Solve by completing the square.**

\[x^4-18 x^2+17=0\]

Hint: Assume \(x^2=t\)**Write the following equation of the form \((x-h)^2+(y-k)^2=r^2\) by completing the square.**

\[x^2+y^2-4 x-6 y+8=0\]

Hint: Group \(x\) terms separately and \(y\) terms separately and then complete the squares.

**Interactive Questions**

**Here are a few activities for you to practice. **

**Select/type your answer and click the "Check Answer" button to see the result.**

**Let's Summarize**

The mini-lesson targetedthe fascinating concept of x squared. We explored x squared,x squared equals, square root, x cubed, what is x Squared x, x 2, x squared times x, x squared plus x squared, x squared symbol, x squared minus x, x squared divided by x, and x squared plus y squared.

The math journey around x squared starts with what a student already knows, and goes on to creatively crafting a fresh concept in the young minds. Done in a way that not only it is relatable and easy to grasp, but also will stay with them forever. Here lies the magic with Cuemath.

**About Cuemath**

AtCuemath, our team of math experts is dedicated to making learning fun for our favorite readers, the students!

Through an interactive and engaging learning-teaching-learning approach, the teachers explore all angles of a topic.

Be it worksheets, online classes, doubt sessions, or any other form of relation, it’s the logical thinking and smart learning approach that we, at Cuemath, believe in.

**Frequently Asked Questions (FAQs)**

## 1.What is a squared minus b squared?

This is given by the difference of squares formula:

\[a^2-b^2=(a+b)(a-b)\]

## 2.What does 3 x squared mean?

3 x squared means \(3x^2\).

Its 3 times \(x^2\).

## 3.How do you type 2 x squared?

2 x squared can be typed as \(2x^2\).

Here, the 2 above \(x\) is a superscript.

## 4.How do you find square root?

To find the square root of a number, we have to see by multiplying which number by itself, we can get the given number.

For example,

\[ \sqrt{9} = \sqrt{3^2} = 3\]